DESIGNING GROUP-BASED CHOREOLOGY LEARNING TOOLS TO IMPROVE THE QUALITY OF LEARNING IN STUDENTS - Sumiani Sumiani (Universitas Negeri Makassar, 2022)
This research answers the problems: 1) How are the learning tools needed by students in the material of the dance textual approach in the Choreology course in the Sendratasik Education Study Program and 2) How to design a Group Investigation-based learning tool for students on the material of the dance textual approach in the Choreology course in the Sendratasik Education Study Program FSD UNM. The learning tools that will be developed in this study use the ADDIE model, which is a model that is commonly used in learning in general, in this study it is only carried out up to the point of design or design. The results of the research are as follows: 1) Learning tools in the form of worksheets needed in the Choreology course in the Sendratasik Education Study Program, Faculty of Art and Design, UNM, are worksheets that can improve the quality of learning. Worksheets are designed based on the Group Investigation learning model which consists of four stages of activity, namely: planning, investigation, presentation, and evaluation. The selection of the Group Investigation model with consideration of opportunities in the design of worksheets can be more varied since the activities in the syntax differ from beginning to end. Thus, it is hoped that the absorption of knowledge, skills, and attitudes in the teaching and learning process can be maximized. 2) The design of worksheets in the Choreology course in the Sendratasik Education Study Program, Faculty of Art and Design, UNM, especially on the competence of identifying change and textual sustainability of dance consists of two types, namely worksheets for groups and worksheets for individuals. The group worksheet consists of four activities, namely: planning the investigation, making an investigation, presenting the results of the investigation, and evaluating. At the stage of making an investigation activity, there is a task sheet for individuals where each member of the group gets the task of one aspect.